Trends in fiber characteristics of Nigerian grown bamboo and its effect on its impact and tensile strengths (2008)
Variations in impact bending and tensile strengths of Bambusa vulgaris (Schrad) with increasing culm height were studied considering its fiber characteristics at the nodes and internodes along the length of the culm. At the nodes, statistical analysis revealed a weak but direct correlation between fiber length and tensile strength while fiber diameter had a strong but inverse relationship with it. Impact bending showed a direct but weak relationship with fiber length while it had an inverse and weak correlation with fiber diameter. For the internodes, a st-'^gn inverse relationship was established between fiber length and tensile strength while fiber diameter showed a direct but weak relationship. Impact bending and fiber length had a strong but inverse correlation while fiber length and impact bending revealed a direct and significant correlation.